Design and evaluation of a multi-sensory representation of scientific data - Varano, Stefania; Zanella, Anita (Frontiers in Education, 2023)
Modern sciences and Astrophysics in particular study objects and phenomena not visible in physical terms, that is they cannot be investigated with the eyes or analogous optical systems. Nevertheless, they make intensive use of visual representations, showing data in a figurative way, using lights, shadows, colours and shapes familiar to the user and aesthetically pleasant. Besides being inaccessible for Blind and Visually Impaired (BVI) users, such figurative visual representation can lead to misunderstandings about the real nature of the represented object, physically invisible, particularly if the representation code is not declared. In this work we argue that multi-sensory representations clearly arbitrary, i.e. that do not aim to imitate reality, are a valid choice for an effective learning and understanding of astronomical science and for an effective meaning-making process for all. The presence of a cognitively challenging code of representation can make the fruition more conscious and attentive, leading to a deeper understanding of the represented reality, also mirroring the search for relevant information proper of basic research. In an equity perspective, multi-sensory representations also create an effective common ground for inclusion among people with diverse abilities, skills and learning styles, in the framework of Universal Design for Learning. In order to investigate our hypothesis we designed two mono-sensory representation (one only haptic and the other only acoustic) and tested them in individual and group workshops with both sighted and BVI users. We then used our results to guide the design of a multi-sensory representation of non-visible astronomical data including visual, acoustic and haptic stimuli. We tested this representation as well, in order to refine and propose it to the public. The result is the exhibit "Sense the Universe", to be used for outreach and education. "Sense the Universe" was part of a museum exhibition attended both by sighted and BVI users, where we collected feedback about the final outcome of our work. Our findings suggest the validity of multi-sensory representations for a truly and effective engagement in scientific learning, both in terms of intelligibility and persistence of scientific contents and of a more equal access to scientific culture.